Increasing Teacher Competence In Using Digital Learning Educational Technology - Nguyen Thanh Giang; Pham Tiet Khanhr (Community Service Akseprin Journal, 2023)
Online learning is considered to be a solution for teaching and learning activities to continue in the midst of current progress. Although it has been agreed, this method has attracted controversy. Teacher readiness is required to be able to teach with the ability to use effective and efficient learning technology, while the fact in the field is that there are still many teachers who are not proficient in using learning technology. The Community Partnership Program will be implemented in the form of providing online training focused on introducing Learning Technology that can be used by school teachers. This online training is expected to help teachers in terms of designing E-learning learning, using Websites and Mobile Applications that support the delivery of teaching materials, helping students become independent students with independent exploration skills, using appropriate applications to evaluate student learning outcomes in the form of assignments, quizzes, and online exams